Analisis Keterkaitan antara Akses Internet, Akses Listrik, dan Produk Domestik Bruto (PDB) di Indonesia Menggunakan Vector Autoregressive Model (VAR) - Abel Gempati; Anisatu Rodiyah; Fatharani Ishlahi Asy Syifa Yovika Putri; Fazila Ghani Revirgin; Pradifta Pilar Putra Maulana (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study examines the relationship between electricity access, internet usage, and Gross Domestic Product (GDP) in Indonesia using the Vector Autoregressive (VAR) method. Access to electricity and the internet is vital for economic growth, though disparities remain, particularly in underdeveloped areas. The findings reveal a significant long-term relationship among the variables, with electricity access enhancing internet usage, which in turn influences economic growth. The Johansen cointegration test confirms their joint movement, while the Granger causality test shows a bidirectional relationship between GDP and electricity access. It is recommended that the government prioritize equitable access to electricity and the internet, improve digital skills, and promote collaboration between public and private sectors to achieve sustainable economic growth.